Profile of Travelers With Preexisting Medical Conditions Attending a Specialist Travel Medicine Clinic in Ireland. Issue 5 (22nd June 2015) - Han, Calvin Teo Jia; Flaherty, Gerard
<x xml:space="preserve">Abstract</x> Background Patients with complex medical comorbidities travel for protracted periods to remote destinations, often with limited access to medical care. Few descriptions are available of their preexisting health burden. This study aimed to characterize preexisting medical conditions and medications of travelers seeking pre‐travel health advice at a specialized travel medicine clinic. Methods Records of travelers attending the Galway Tropical Medical Bureau clinic between 2008 and 2014 were examined and information relating to past medical history was entered into a database. Data were recorded only where the traveler had a documented medical history and/or was taking medications. Results Of the 4, 817 records available, 56% had a documented medical history and 24% listed medications. The majority of travelers with preexisting conditions were female. The mean age of the cohort was 31.68 years. The mean period remaining before the planned trip was 40 days. Southeast Asia was the most popular single destination, and 17% of travelers with medical conditions were traveling alone. The most frequently reported conditions were allergies (20%), insect bite sensitivity (15%), asthma (11%), psychiatric conditions (4%), and hypertension (3%). Of the 30 diabetic travelers, 14 required insulin; 4.5% of travelers were taking immunosuppressant drugs, including corticosteroids. Half of the female travelers were taking the oral contraceptive pill while 11 travelers were pregnant at the time of their pre‐travel consultation. Conclusions This study provides an insight into the medical profile of travelers attending a travel health clinic. The diverse range of diseases reported highlights the importance of educating physicians and nurses about the specific travel health risks associated with particular conditions. Knowledge of the effects of travel on underlying medical conditions will inform the pre‐travel health consultation.